The influence of pregnant women's physical activity on selected perinatal parameters - Anna Wojtyla; Martyna Mączka (Journal of Education, Health and Sport, 2023)
AIM OF THE PAPER: Evaluation of influence of physical activity on selected perinatal parameters.